Physical activity levels and activity preferences of a cohort of South African individuals living with HIV - R. Roos; H. Myezwa; H. van Aswegen (AOSIS, 2013)
Physical inactivity is a risk factor for many lifestyle diseases. It is still poorly understood in individuals living with HIV. The aims of this study were to evaluate the physical activity levels of individuals living with HIV on antiretroviral therapy (ARV) and to assess their physical activity preferences. An observation study was done from October 2010 to June 2012 at a large urban HIV clinic in Johannesburg where 205 individuals were consecutively sampled. Physical activity was assessed with the Yamax SW200 pedometer over a seven-day period. The mean age of the sample was 38 (± 9.5) years, CD4 count 285.1 (± 157.9) and time on ARV 8.7 (± 2.3) months. Physical activity of the sample was reduced at 7673.2 (± 4017.7) steps per day with women walking less than men [6993.3 (± 3462.6) and 10076.3 (± 4885.6) respectively]. Eight individuals (3.9%) did formal sporting activities and a hundred and twenty-three individuals (60%) did some form of exercise. Walking (45.5%, n=56) and running (26.8%, n=33) were most frequently reported. Physical inactivity was present in the majority of the sample and interventions including activity preferences of individuals could be strategies to address this health concern.